Kinerja Dosen: Analisis dari Aspek Budaya Kerja, Kompetensi dan Disiplin Kerja di Universitas Muhammadiyah Prof Dr. HAMKA - Muchdie; Bambang Dwi Hartono; Muhammad Arief Darmawan (Jurnal Utilitas, 2019)
This research aims to reveal and analyze the influence of Work Culture, Competence and Work Discipline on the performance of lecturers. The method used in this descriptive study is quantitative research, survey methods, questionnaires and path analysis techniques. The results of hypothesis testing are a significant direct effect of Work Culture (X1) on Work Discipline (X2) is 42%. Then the significant direct effect of Competence (X2) on Work Discipline (X3) is 46.65%. There is a direct and indirect influence of Work Culture (X1) on Work Discipline (X3) through Competence (X2) is 44.6%. Competence (X2) has a significant direct effect on Performance (X4) is 56%. And the direct and indirect influence of Work Culture (X1) on Performance (X4) through Competence (X2) produces a significant effect is 48.08%. Lecturer performance related to the 3 indicators in this study, namely time, quality and quantity can improve the implementation of education and teaching, research and community service. Increasing the competence of lecturers to carry out a job professionally affects lecturers competence in pendagogik competence, professional competence, personality competence, and social competence. Work discipline indicators in complying with work rules and procedures, on-time attendance, work completion, and the usage of facilities and infrastructure have a significant contribution to improving lecturer performance through competence.